2019
DOI: 10.3390/rs11172007
|View full text |Cite
|
Sign up to set email alerts
|

Study of a High Spectral Resolution Hyperspectral LiDAR in Vegetation Red Edge Parameters Extraction

Abstract: Non-contact and active vegetation or plant parameters extraction using hyperspectral information is a prospective research direction among the remote sensing community. Hyperspectral LiDAR (HSL) is an instrument capable of acquiring spectral and spatial information actively, which could mitigate the environmental illumination influence on the spectral information collection. However, HSL usually has limited spectral resolution and coverage, which is vital for vegetation parameter extraction. In this paper, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…The spectra for ore samples classification cover from 650 to 680 nm with six channels with 5 nm resolution. The 655-740 nm range for plant leaves in Dataset 4 was consistent with the previous studies in that the red edge position usually locates in red band spectrum normally from 680 to 720 nm [13,23,34,35]. Chlorophyll contained in plants absorbs a large amount of light in the We found that the selected channels for different materials varied.…”
Section: The Selected Channelssupporting
confidence: 89%
See 3 more Smart Citations
“…The spectra for ore samples classification cover from 650 to 680 nm with six channels with 5 nm resolution. The 655-740 nm range for plant leaves in Dataset 4 was consistent with the previous studies in that the red edge position usually locates in red band spectrum normally from 680 to 720 nm [13,23,34,35]. Chlorophyll contained in plants absorbs a large amount of light in the We found that the selected channels for different materials varied.…”
Section: The Selected Channelssupporting
confidence: 89%
“…The 655-740 nm range for plant leaves in Dataset 4 was consistent with the previous studies in that the red edge position usually locates in red band spectrum normally from 680 to 720 nm [13,23,34,35]. Chlorophyll contained in plants absorbs a large amount of light in the visible spectrum and it becomes almost transparent at wavelengths greater than 700 nm [13].…”
Section: The Selected Channelssupporting
confidence: 88%
See 2 more Smart Citations
“…HSL hardware prototype in full band was designed at the Finnish Geodetic Institute, which was used for vegetation remote sensing in 2012 [13]. Recently, various applications of HSL have been reported, such as coal/rock classification [15], vegetation detection [14], vegetation index extraction [16], architecture preservation [17], and ore classification [18].…”
Section: Introductionmentioning
confidence: 99%